L’impact de la Banque du Canada sur la disponibilité du crédit bancaire : 1967-1976 - Théoret, Raymond (L'Actualité économique, 1979)
In this article we want to verify if Bank of Canada's actions on the availability of credit were efficient from 1967 to 1976. During this period, the interest rate was chiefly used to maintain balance of payments equilibrium and the Bank of Canada was trying to affect internal credit conditions (here banks' loans) through its effect on the chartered banks' liquid asset ratio. However, this ratio is an imperfect indicator of the availability of banks' credit. Chartered banks have in fact many techniques to obtain liquidities: the whole of these constitutes their liability management mechanism. By this way, they can immune themselves from a restrictive monetary policy which operates via the liquid asset ratio. The degree of accommodation of loans is also another factor to consider when studying the impact of the Bank of Canada on banks' loans. It is evident that a high degree of accommodation of loans is a serious obstacle to monetary policy: liquidity management is probably pushed very far in this case. Our theoretical model takes into account these considerations. And the estimation of this model shows that loans have little reacted to Bank of Canada's actions. The degree of loans accommodation was high and consequently banks checked the Bank of Canada's policy by their liquidity management mechanism.